Pengaruh Good Corporate Governance Pemoderasi, Struktur Modal dan Kepemilikan Manajerial Terhadap Nilai Perusahaan - Alansyah, Spani; Sugiyanto, Sugiyanto (Peneliti.net, 2023)
The purpose of this study is to ascertain how management ownership, capital structure, and outstanding corporate governance affect the firm value of companies listed on the Indonesia Stock Exchange between 2017 and 2021. The purposive sampling technique was used to compile a sample of 21 businesses. Multiple linear regression analysis is the method of analysis used. According to the study's findings, capital structure and managerial ownership have an impact on firm value simultaneously, capital structure has a significant impact on firm value, managerial ownership has no impact on firm value, and good corporate governance can strengthen this relationship. (5) Managerial Ownership and Corporate Value are not able to be strengthened or weakened by good corporate governance.